Comparative in vitro susceptibility of clinical Leishmania isolates to miltefosine and oleylphosphocholine - Khamesipour, Ali; Tasbihi, Minoo; Mohammadi, Akram Mir Amin; Dixon, Jodie; Clark, David J.; Staines, Henry M.; Krishna, Sanjeev; Yardley, Vanessa; Croft, Simon L.; Alexander, Neal; Van Bocxlaer, Katrien (Frontiers in Pharmacology, 2025)
Cutaneous leishmaniasis (CL) is a neglected tropical disease caused by protozoan parasites of the genus Leishmania. It poses a significant global health burden, particularly because treatment options are limited. More effective and safer treatments are urgently needed. In previous studies, oleylphosphocholine (OlPC), a novel investigational compound structurally related to miltefosine, exhibited comparable activity to miltefosine in intramacrophage assays across various CL-causing laboratory strains and demonstrated superior efficacy in an experimental CL model. This study investigated the in vitro activity of OlPC against clinical isolates of Leishmania spp., comparing its activity with standard anti-leishmanial drugs, including miltefosine, amphotericin B, and pentavalent antimonial agents. Seventy ex vivo isolates (L. major and L. tropica) obtained directly from CL patients before any treatment were used to capture the diversity of drug susceptibilities in circulating parasite populations. Dose-response curves were fitted using a four-parameter log-logistic model to estimate EC50 and EC90 values. Additionally, a linear mixed-effects model was applied to examine the influence of drug type and species on EC50 values while accounting for within-isolate variability. Our findings indicate that OlPC exhibits potent in vitro anti-leishmanial activity, exceeding that of miltefosine in our in vitro intramacrophage model. To facilitate similar analyses, we provide a dedicated wrapper function in R designed to simplify curve fitting and parameter estimation, making the process more accessible to researchers.